Pemanfaatan buah lontar untuk pengembangan kewirausahaan berbasis ecopreneurship melalui home industry pada ibu-ibu PKK di Makassar - Jokebet Saludung; Muhammad Yahya (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This Community Partnership Program (PKM) isimplemented in 2018 in Tidung village by applying the resultsof research in 2017. The aim is to provide training to thecommunity to make bluders cake, mabel and pudding usinglontar (palmyra fruit or talak) as the main ingredients with theintention that the community got the skills to be independentto make home industry products to increase family income.Lontar is available on their neighbourhood but it is wasted inits season and the price is very cheap because the communitydoes not know its benefit and nutritional content. Therefore,after being examined, the results must be trained in thecommunity partnership program to disseminate its use to befavored by the community and increase the selling value andeconomic value of lontar. Previous research results indicatethat the cake is very popular because it is worthy of beingapplied in this PKM. The training went very well, the resultswere also very maximum and the products were liked bywomen of Family Welfare Empowerment as the trainees in thiPKM. They are enthusiastic in making talak pudding, talakbluder, and mabel talak. The training involved 31 women ofFamily Welfare Empowerment which was originally plannedfor 20 people. After the training, they were given theopportunity to work in groups to make products. After theresults were evaluated it turned out that they had tried to makeit themselves. The obstacles found were the need for capitalassistance and tools for entrepreneurship. This still needs helpfrom the local government or investors who want to help thecommunity to do entrepreneurship.